Asset management system (ISO 55001) and Total Productive Maintenance (TPM): a discussion of interfaces for maintenance management - Silva, Renan Favarão da; Souza, Gilberto Francisco Martha de (Revista Gestão da Produção Operações e Sistemas, 2020)
In the current globalized scenario, high productivity is a competitive factor for the survival and success of organizations. Ensuring the physical assets of the company is performing its functions while minimizing the occurrences of quality defects and breakdowns is a challenge in the maintenance management. Among the diffused approaches is Total Productive Maintenance (TPM) and, more recently, the asset management system (AMS) of the international standard series ISO 55000. The objective of this work, therefore, is to discuss the interfaces between the approaches in order to clarify the correlations and sufficiency of the TPM for an AMS. For this, a three-part methodology was structured: content review, correlation of the themes and discussion of interfaces. It was observed that TPM is a model for maintenance management and widely used in the manufacturing industries, while the AMS is a broader approach. Therefore, it was evidenced TPM can be an applicable management model to handle the maintenance requirements of ISO 55001, although it is not sufficient by itself. Thus, it is expected that this work will clarify the organizations on the non-exclusive nature of two themes.